Intellectual property policy on pharmaceutical products: a view in the beginning of the 2000 decade - DOI: 10.3395/reciis.v2i2.191en - Sergio M Paulino de Carvalho; Sergio Salles-Filho; Antonio Marcio Buainain; Maria Beatriz Bonacelli; Marcos Paulo Fuck (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2009)
This paper aims at an analysis of the intellectual property policy in the health field by emphasizing the program of production and distribution of antiretrovirals and the generic drugs market, also reviewing the process of articulation and implementation of the intellectual property policy in this sector. From a methodological viewpoint, the paper favors the analysis of data related to the structuring of the pharmaceutical products market and of impacts both from the new institutionality and the intellectual property policies developed by the Ministry of Health in the first half of the 2000's decade.